Fundamentals of Entreoreneurship ENT 300 : Florentine De’ Lily / Lily Azniza Azlan - Azlan, Lily Azniza (2021)
My objective in building this Florentine De’ Lily business is to offer my new recipes to my customers and based on how Asians like them. Eventually I decide to proceeds with the Florentine cookies business as I believe that this business has a lot of strengths and opportunities compared to the others. As for my target market and my prospects for business, the major target market is for customers aged about 25 and below who are married men and women. This is due to the women and men which is already married, they would prefer to purchase rather than make as they are very busy working and need to take care of their children. I also realize it is difficult for everybody to reach at once, reducing my emphasis to a core audience allows my firm to develop a message strategy that is directed at the kind of products that are most likely to become customers. I also believe my business will succeed as my products have several competitive advantages, such as extremely exceptional handmade cookies which not only taste wonderful, but which also look intriguing and appealing. Also, all of my biscuits include a tiny added touch as a little sugar ball as a food sprinkle on topping. As for the target profit, I target 28 containers will be sold at a price of RM15. I am thankful my business is running smoothly as my sales have surpassed what I was targeting with having got 40 containers all at once. 40 containers have been sold multiplied by the price of RM15 there is a profit of rm600.